What’s inside the net? insights into fish bycatch diversity in the Antarctic krill fishery - María Lorena Romero Martínez; William D. K. Reid; Martin A. Collins; Katia Lizeth Treviño Cuellar; William P. Goodall-Copestake; James M. Clark; Benedict Viney; Susan Gregory; Kate Owen; Philip R. Hollyman (Polar Biology, 2026)
An ecosystem-based approach to fishery management requires, inter alia, knowledge of fishery impacts on both target and non-target species, as well as the wider ecosystem. To support management of the Antarctic krill fishery, we present a robust reference dataset for identifying fish species caught as bycatch. By combining morphological and molecular taxonomic identification, 53 fish species in 44 genera and 11 families were confidently identified. Our dataset extends the DNA barcode library of Sub-Antarctic and Antarctic fish species and provides a foundation for developing an enhanced identification guide for larval fish to be used by observers on board krill fishing vessels. Phylogenetic relationships were inferred from two commonly used barcode markers, the mitochondrial cox1 and the non-coding control region. We observed clear phylogenetic relationships, highlighting coherent placements of notothenioids, myctophids, Aulopiformes, Gadiformes and Zoarcoidei. The results suggest a discrepancy between observer-based and genetic identifications, with 20.6% of records representing misidentifications in the fishing seasons 2021/2022 and 2022/2023. Graphical Abstract Graphical abstract: illustrated by ©Louise Merquiol-Hatsya illustrations